THE IMPACT OF DIGITAL LEADERSHIP AND ORGANIZATIONAL FLEXIBILITY ON IMPROVING JOB PERFORMANCE: A SAMPLE OF CLUB PRESIDENTS IN THE IRAQI FOOTBALL LEAGUE - Mustafa Qasim Al-Malji (PT. Antis International Publisher, 2026)
Objective: This study aimed to analyze the impact of digital leadership and organizational flexibility on improving job performance in sports clubs, through a field study on a sample of club presidents and coaches in the Iraqi Football League. Method: The study adopted a descriptive-analytical approach, and data were collected using an electronic questionnaire designed according to a five-point Likert scale. The study sample consisted of (103) individuals, and the data were analyzed using statistical packages. The SPSS version 25 and AMOS version 25 were used, along with Structural Equation Modeling (SEM), to test the study hypotheses. Results: The descriptive analysis revealed that the level of digital leadership practice and organizational flexibility in sports clubs was moderate to high, while the level of job performance was relatively high. Reliability testing also demonstrated a high degree of internal consistency in the research instrument, with a Cronbach's alpha coefficient of 0.950, indicating its reliability. The correlation analysis revealed strong and statistically significant positive correlations between the three study variables. The impact analysis also showed that digital leadership has a very good effect on how well people do their jobs with a score of 0.525. Novelty: This indicates that adopting digital leadership practices and enhancing organizational flexibility clearly contribute to improving job performance within sports institutions.